2009
DOI: 10.1213/ane.0b013e3181b7c4f6
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine Spinal Anesthesia Is Not Antagonized by Ondansetron Pretreatment

Abstract: Ondansetron had no effect on the subarachnoid sensory or motor block produced by ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Our results agree with those of Paraskeva et al 6 who found that pretreatment with ondansetron the night before surgery and prior to spinal anaesthesia with ropivacaine had no effect on sensory block. Ropivacaine is a similar local anaesthetic to bupivacaine but less potent 9 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with those of Paraskeva et al 6 who found that pretreatment with ondansetron the night before surgery and prior to spinal anaesthesia with ropivacaine had no effect on sensory block. Ropivacaine is a similar local anaesthetic to bupivacaine but less potent 9 .…”
Section: Discussionsupporting
confidence: 93%
“…Pretreatment with ondansetron and granisetron enhances regression of sensory block after intrathecal administration of 5% hyperbaric lignocaine 4 and hyperbaric bupivacaine 5 respectively. In contrast, pretreatment with high dose ondansetron has no effect on the duration of motor and sensory block after subarachnoid anaesthesia with ropivacaine 6 .…”
mentioning
confidence: 77%
“…This finding was consistent with the results of our previous study, where no difference was observed in the ondansetron group compared to placebo, regarding block characteristics in male patients presenting for transurethral surgery under spinal anesthesia with ropivacaine. 24 Moreover, no difference was observed in the occurrence of shivering and this finding is consistent with the results of a meta-analysis by Zhou et al, in which, a favorable antiemetic effect of ondansetron in spinal anesthesia for cesarean section, was recorded. 14…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have also been seen with ondansetron administered to patient prior to spinal anesthesia. [81516]…”
Section: Discussionmentioning
confidence: 99%
“…Similar lack of effects on motor blockade has also been seen in other studies using other 5-HT3 receptors antagonists. [789151619]…”
Section: Discussionmentioning
confidence: 99%